1983
DOI: 10.1148/radiology.146.2.6294736
|View full text |Cite
|
Sign up to set email alerts
|

Multilocular cystic nephroma: a radiographic-pathologic correlation of 58 patients.

Abstract: Clinical radiographic, and pathologic findings of multilocular cystic nephroma (MLCN) in 58 patients are presented. The lesion that affects predominantly boys in childhood and women in adulthood is usually solitary but rarely can be multiple, and it commonly occurs as an asymptomatic mass, occasionally with hematuria. Tumors may grow slowly over years or rapidly within months. A mass that is usually identified on plain radiographs occasionally has curvilinear calcification. Excretory urography and retrograde p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0
5

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(61 citation statements)
references
References 0 publications
2
54
0
5
Order By: Relevance
“…The tumor was originally described by Edmunds in 1892 as a "cyst adenoma" and since then, the spectrum of histologic findings and multiple theories of the pathogenesis of cystic nephroma have given rise to many synonymous terms, including benign multilocular cystic nephroma and cystic nephroblastoma. 5,6 Less than 200 cases have been reported till date in the international literature. 4 Studies have confirmed a biphasic age and sex distribution: two-thirds of multi-locular cystic renal tumors occur in a predominantly male pediatric population between three months and two years of age; approximately one-third occurs in the female population, with a peak in the fifth and sixth decades of life.…”
Section: Casementioning
confidence: 99%
“…The tumor was originally described by Edmunds in 1892 as a "cyst adenoma" and since then, the spectrum of histologic findings and multiple theories of the pathogenesis of cystic nephroma have given rise to many synonymous terms, including benign multilocular cystic nephroma and cystic nephroblastoma. 5,6 Less than 200 cases have been reported till date in the international literature. 4 Studies have confirmed a biphasic age and sex distribution: two-thirds of multi-locular cystic renal tumors occur in a predominantly male pediatric population between three months and two years of age; approximately one-third occurs in the female population, with a peak in the fifth and sixth decades of life.…”
Section: Casementioning
confidence: 99%
“…Under the age of 5 years, MCN occurs most frequently in males, whereas the adult group has a female predominance between the ages of 40 and 60. The most common presenting symptoms are a painless abdominal mass, abdominal or flank pain, and occasionally hematuria (2).…”
Section: Commentsmentioning
confidence: 99%
“…Mostly atypical features were noted: flank dullness, colic pain, weight loss, hematuria, hypertension or urinary infection. In 6 been used: renal multilocular cyst, benign multilocular cystic nephroma, renal cystadenoma, partial polycystic kidney, and polycystic nephroblastoma were the most commonly used, but quite confusing [2][3][4][5][6], Cystic nephroma has a special age and sex distribu tion. Children not older than 4 years are males in 75% of the cases.…”
Section: Clinical Findingsmentioning
confidence: 99%
“…Nevertheless some of these criteria will have to be adated because recently 3 bilateral cystic nephromas have been reported [2,13,14] and reports of cystic ne phroma with a Wilms' tumor in the remaining kidney have been published [2,3,15], The reports of renal ade nocarcinoma found in cystic nephroma [2,16,17] are probably adenocarcinoma with cystic degeneration due to tumor necrosis and/or hemorrhage. Cystic nephroma, certainly in the adult, is a benign neoplastic lesion of the kidney originating in the metanephrogenic tissue, out of which the functional renal parenchyma normally develops.…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation